Activated carbons obtained by environmentally friendly activation using solar energy for their use in neutral electrolyte supercapacitors. (15th August 2022) - Lobato-Peralta, Diego Ramón; Ayala-Cortés, Alejandro; Longoria, Adriana; Pacheco-Catalán, Daniella Esperanza; Okoye, Patrick U.; Villafán-Vidales, Heidi Isabel; Arancibia-Bulnes, Camilo Alberto; Cuentas-Gallegos, Ana Karina
Abstract: Agave Angustifolia leaves, an agro-industrial waste from alcoholic beverages manufacture, were used as a lignocellulosic precursor to produce activated carbons for neutral electrolyte supercapacitor cells. The Agave precursor was impregnated with K2 CO3 to different ratios as an environmentally friendly activating agent and pyrolyzed in a solar furnace at different temperatures, using concentrated solar energy as the heat source. The results show that the temperature and the activating agent concentration tailor the textural and hydrophilic properties of the carbons for energy storage in supercapacitors. Electrochemical tests in 3-electrode cells using a neutral electrolyte (1 M Na2 SO4 ) indicate that the carbons obtained between 600 and 800 °C, with different activating agent ratios, are suitable for energy storage purposes, reaching specific capacitance values higher than 200 F g −1 . The results in 2-electrode supercapacitors showed that these carbons have better electrochemical performance than commercial carbon. The agave leaf activated carbons delivered up to 15 W h kg −1 at a specific current of 0.25 A g −1 and have specific power close to 1100 W kg −1 at 2.00 A g −1 . The long-term cycling of these devices demonstrated good behavior when a specific current of 0.5 A g −1 was applied, showing a Coulombic efficiency close to 100% and energy efficiency higher than 60%. Hence, activated carbons obtained using solar energy, an environmentally friendly activating agent, and a neutral electrolyte enable the development of greener supercapacitor devices. Graphical abstract: Unlabelled Image Highlights: Solar radiation allows to produce activated carbons employing renewable energy. K2 CO3 is an excellent environmentally friendly activating agent to improve porosity. Neutral aqueous electrolyte allows wide potential windows. Agave leaf activated carbons delivered more energy than a commercial one.